PROSES PEMEROLEHAN BAHASA: DARI KEMAMPUAN HINGGA KEKURANGMAMPUAN BERBAHASA - Indah, Rohmani Nur (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2008)
Studies on language acquisition become the pillar of Psycholinguistics as a branch of Applied Linguistics that deals with the relationship between human’s thought and language as well as how human beings comprehend, acquire and develop their language. Language acquisition does not merely involve children’s first or second language development, but also temporer language disorder –which does not belong to permanent language disorder. Deviation on language development to some extent gets little attention from psycholinguists. Most references on psychology of language discuss language disorder in general, whereas the current issues on this area are still rarely found. The following article deciphers what and how language acquisition can be done and cannot be completed.